Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12890-017-0397-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of lung function and COPD with peripheral blood DNA methylation in population based studies

Abstract: BackgroundEpigenetic variations in peripheral blood have potential as biomarkers for disease. This systematic review assesses the association of lung function and chronic obstructive pulmonary disease (COPD) with DNA methylation profiles in peripheral blood from population-based studies.MethodsOnline databases Medline, Embase, and Web of Science were searched. Google Scholar was searched to identify grey literature. After removing duplicate articles, 1155 articles were independently screened by two investigato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
(117 reference statements)
1
26
0
Order By: Relevance
“…This partially agrees with epigenetic analysis of differentially methylated CpG sites in blood. A systematic review did not find any consistent association for lung function or COPD [ 39 ]. Furthermore, this site was not found to be smoking-specific in a Korean cohort of COPD patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This partially agrees with epigenetic analysis of differentially methylated CpG sites in blood. A systematic review did not find any consistent association for lung function or COPD [ 39 ]. Furthermore, this site was not found to be smoking-specific in a Korean cohort of COPD patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of epigenome-wide methylation studies have been performed in whole blood, and few data are available on DNA methylation in whole lung tissue and lung tissue-specific cell types. Although it has been widely established that cigarette smoke affects DNA methylation [90] and that COPD is highly associated with cigarette smoke exposure, in a recent systematic review by MACHIN et al [91], no consistent differences were found in DNA methylation in peripheral blood in association with COPD or lung function. Therefore, the role of DNA methylation in COPD and hence the role of age-associated differences in DNA methylation in COPD remain unclear.…”
Section: Epigenetic Changesmentioning
confidence: 95%
“…[7][8][9] Moreover, there has been little consistency between the positive findings reported. 9,10 Studies of lung tissue 5,8 have been constrained by sample availability, with the largest study to date comprising 160 subjects. 5 Inconsistency amongst the results of the peripheral bloodbased studies 3,6,7,9,11 is likely to be due to a number of factors, including small sample size (e.g., two studies had less than 200 samples) 6,11 and/or investigation of a relatively small number (~27,000) of CpG loci.…”
Section: Introductionmentioning
confidence: 99%
“…12 Differences in spirometric measures, definitions of COPD, study population characteristics and study design, in particular in the method used to adjust for smoking history, are also likely to be important sources of variation. 9,10 Here we sought to identify robust associations by assessing methylation in a large single cohort sample, applying a more rigorous correction for smoking history and by performing sensitivity analyses. In contrast to prior studies, we used the recently released Illumina EPIC array, which interrogates over 850,000 methylation sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation